Prognostication of Learning Curve on Surgical Management of Vasculobiliary Injuries after Cholecystectomy - Abu Bakar Hafeez Bhatti; Faisal Saud Dar; Haseeb Zia; Muhammad Salman Rafique; Nusrat Yar Khan; Mohammad Salih; Najmul Hassan Shah (International Journal of Hepatology)
Background. Concomitant vascular injury might adversely impact outcomes after iatrogenic bile duct injury (IBDI). Whether a new HPB center should embark upon repair of complex biliary injuries with associated vascular injuries during learning curve is unknown. The objective of this study was to determine outcome of surgical management of IBDI with and without vascular injuries in a new HPB center during its learning curve. Methods. We retrospectively reviewed patients who underwent surgical management of IBDI at our center. A total of 39 patients were included. Patients without (Group 1) and with vascular injuries (Group 2) were compared. Outcome was defined as 90-day morbidity and mortality. Results. Median age was 39 (20–80) years. There were 10 (25.6%) vascular injuries. E2 injuries were associated significantly with high frequency of vascular injuries (66% versus 15.1%) (P=0.01). Right hepatectomy was performed in three patients. Out of these, two had a right hepatic duct stricture and one patient had combined right arterial and portal venous injury. The number of patients who developed postoperative complications was not significantly different between the two groups (11.1% versus 23.4%) (P=0.6). Conclusion. Learning curve is not a negative prognostic variable in the surgical management of iatrogenic vasculobiliary injuries after cholecystectomy.